The impact of microcredit services on the rural economy: Evidence from Albania: Array - Muharremi, Oltiana; Madani, Filloreta (Acta Universitatis Danubius. Œconomica, 2021)
This study's main objective is to explore microfinance services' impact on Albania's rural creditors. Agriculture is turning into an important economic sector for Albania in recent years. This sector is still the basis of income for most of the population and serves as an essential employment source. The study was conducted among a convenience sample of 384 rural microfinance creditors that self-administered and completed survey questionnaires. The study found that microfinance activities significantly contributed to increasing the business economic and financial conditions and improving the living standard and savings. The Albanian government, microfinance institutions, and other international organizations are jointly undertaking a series of programs and projects to create subsidized loans for rural area residents. This demographic group continually faces challenges. Through an empirical analysis, the research paper aims to assess the impact that microcredit has had on rural areas, the challenges these areas face, and some of the elements that may influence the improvement of borrowing conditions in the future.